Quantitative evaluation of the seismicity in seismogenic sources of the Circum Pacific Rim - KORAVOS, G. CH.; TSAPANOS, T. M.; HATZIDIMITRIOU, P. M.; PAPAIOANNOU, C. A. (Bulletin of the Geological Society of Greece, 2001)
A quantitative measurement of the seismicity is undertaken along the seismogenic sources of the south and central America, as well as of Japan, Taiwan and Philippine islands. The mean return period, Τ , is considered as measure of seismicity. For this purpose the whole process (method of mean value) and the part process (first asymptotic distribution of Gumbel’s extreme values) techniques are adopted. The seismicity is evaluated for both shallow and intermediate focal depth shocks which occurred in the examined sources. The a and b values of the magnitude-frequency relationship are estimated for each source. The obtained results show that large welldefine zones of the mean return periods are dominated in the central and south America, while this is not so strong in the areas of Japan, Taiwan and Philippine islands, which probably due to the different tectonic setting of the areas (Tsapanos, 1990).